Antidepressant and Anti-Neuroinflammatory Effects of Bangpungtongsung-San - Park, Bo-Kyung; Kim, No Soo; Kim, Yu Ri; Yang, Changsop; Jung, In Chul; Jang, Ik-Soon; Seo, Chang-Seob; Choi, Jeong June; Lee, Mi Young (Frontiers in Pharmacology, 2020)
Bangpungtongsung-san (BTS) is a traditional Korean medicine consisting of 18 herbs, some which have antidepressant effects. Here, we used an animal model of reserpine-induced depression and lipopolysaccharide (LPS)-stimulated BV2 microglia to assess the anti-depressant and anti-neuroinflammatory effects of BTS. Aside from a control group, C57BL/6 mice were administered reserpine (0.5 mg/kg) daily for 10 days via intraperitoneal injection. BTS (100, 300, or 500 mg/kg), vehicle (PBS), or fluoxetine (FXT, 20 mg/kg) was administered orally 1 h before reserpine treatment. Following treatment, a forced swimming test (FST), tail suspension test (TST), and open field test (OFT) were performed, and immobility time and total travel distance were measured. Administration of BTS not only reduced immobility time in the FST and TST but also significantly increased the total travel distance in the OFT. Furthermore, reserpine-treated mice showed significantly elevated serum levels of corticosterone, a stress hormone; however, treatment with BTS significantly reduced corticosterone levels, similar to FXT treatment. Serotonin in reserpine-treated mice was significantly reduced compared to that in control mice, while BTS mice exhibited increased serotonin levels. BTS mice showed increased expression of brain-derived neurotrophic factor (BDNF) and a higher ratio of phosphorylated cAMP response element-binding protein (p-CREB) to CREB (p-CREB/CREB) in the hippocampus. Additionally, reserpine-treated mice exhibited significantly elevated mRNA levels of pro-inflammatory cytokines, but BTS mice showed reduced mRNA levels of interleukin (IL)-1β, IL-6, and tumor necrosis factor (TNF)-α in the hippocampus. To further demonstrate the anti-neuroinflammatory effects of BTS in vitro, we examined its anti-neuroinflammatory and neuroprotective effects in lipopolysaccharide (LPS)-stimulated BV2 microglia. BTS significantly reduced the levels of NO, inducible nitric oxide synthase (iNOS), cyclooxygenase (COX)-2, TNF-α, IL-1β, and IL-6 in a dose-dependent manner via a decrease in the expression of nuclear factor (NF)-κB p65. Furthermore, the neuroprotective factor heme oxygenase-1 (HO-1) was upregulated via the nuclear factor-E2-related factor 2 (NRF2)/CREB pathway. Taken together, our data suggest that BTS has considerable potential as an anti-neuroinflammation and antidepressant agent, as it has clear effects on depressive behaviors and associated factors caused by reserpine-induced depression.